Hubungan kecemasan bertanding terhadap akurasi service atlet bola voli marongge sumbawa tahun 2025 - Yogi Putra Pratama; Soemardiawan; Muhammad Ikhsan (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2025)
This study aimed to determine the relationship between competitive anxiety and service accuracy of volleyball athletes in Marongge, Sumbawa, in 2025. This research used a quantitative descriptive method with an ex post facto research design. The sample consisted of 12 volleyball athletes selected using a population study technique. The research instruments included a competitive anxiety questionnaire and a volleyball service accuracy test from the American Association of Health, Physical Education and Recreation (AAHPER). The data were analyzed using the Product Moment correlation technique. The results showed a correlation coefficient of 0.762 with a significance value of 0.04 (<0.05), indicating a significant relationship between competitive anxiety and service accuracy. The coefficient of determination was 58.01%, meaning that competitive anxiety contributed 58.01% to the service accuracy of the athletes. It can be concluded that competitive anxiety has a strong relationship with the service accuracy of volleyball athletes in Marongge, Sumbawa, in 2025.